1991
DOI: 10.1152/jn.1991.66.4.1422
|View full text |Cite
|
Sign up to set email alerts
|

Spatial orientation of the vestibular system: dependence of optokinetic after-nystagmus on gravity

Abstract: 1. Monkeys received optokinetic stimulation at 60 degrees/s about their yaw (animal vertical) and pitch (animal horizontal) axes, as well as about other head-centered axes in the coronal plane. The animals were upright or tilted in right-side-down positions with regard to gravity. The stimuli induced horizontal, vertical, and oblique optokinetic nystagmus (OKN). OKN was followed by optokinetic after-nystagmus (OKAN), which was recorded in darkness. 2. When monkeys were tilted, stimulation that generated horizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
120
2

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(133 citation statements)
references
References 31 publications
11
120
2
Order By: Relevance
“…The axis-shift component is very small in humans during both optokinetic and canal stimulation. In addition, this axis-shift seems to be "economical" in the sense that the eye movement rotation axis always shifts toward alignment with gravity "through the smallest angle," as was suggested in our recent model of reflexive eye responses to visual-vestibular interactions and by numerous experimental investigations (Angelaki and Hess 1994;Dai et al 1991;Fetter FIG. 9.…”
Section: Influence Of Head Orientation On Eye Movement Responsesmentioning
confidence: 64%
See 1 more Smart Citation
“…The axis-shift component is very small in humans during both optokinetic and canal stimulation. In addition, this axis-shift seems to be "economical" in the sense that the eye movement rotation axis always shifts toward alignment with gravity "through the smallest angle," as was suggested in our recent model of reflexive eye responses to visual-vestibular interactions and by numerous experimental investigations (Angelaki and Hess 1994;Dai et al 1991;Fetter FIG. 9.…”
Section: Influence Of Head Orientation On Eye Movement Responsesmentioning
confidence: 64%
“…It has been observed that the eye rotation axis of reflexive eye movements tends to shift toward alignment with gravity in response to either 1) optokinetic stimulation in humans (Furman and Koizuka 1994;Gizzi et al 1994;Wei et al 1994) and monkeys Dai et al 1991;Raphan and Cohen 1988) or 2) canal stimulation in humans (Fetter et al 1992;Furman and Koizuka 1994;Harris and Barnes 1987;Zupan et al 2000) and monkeys (Angelaki and Hess 1994;Jaggi-Schwarz et al 2000;Young 1992, 1995;Merfeld et al 1993a;Wearne et al 1999). The axis-shift component is very small in humans during both optokinetic and canal stimulation.…”
Section: Influence Of Head Orientation On Eye Movement Responsesmentioning
confidence: 99%
“…Second, vestibularly driven vertical eye movements require the coordination of two semicircular canal planes and four extraocular muscle pairs, compared with the single canal plane and two extraocular muscle pairs required for pure horizontal eye movements. Third, horizontal and vertical OKAN are maximal at different head orientations with respect to the gravitoinertial axis (Dai et al 1991;Raphan and Cohen 1985;Raphan and Sturm 1991). In an upright posture, horizontal OKAN is maximal and vertical OKAN is minimal (Cohen et al 2002;Raphan and Cohen 1988).…”
Section: Introductionmentioning
confidence: 95%
“…During optokinetic stimulation, visual pathways are activated whose dependence on gravity signals has not been determined. If the gyroscopic properties of the vestibular system were limited to the "yaw axis eigenvector of the velocity storage integrator" as proposed by Raphan and colleagues, its manifestation in the oculomotor output would indeed only reflect a central representation of the spatial vertical (Dai et al, 1991). If, however, all semicircular canal signals were spatially transformed into a signal representing head motion in space, the functional ramifications of such processing would be much more intriguing.…”
Section: Presence Of Inertial Vestibular Signals In the Vormentioning
confidence: 99%
“…For example, head tilts at slow velocity taking 4-6 set to complete did no longer elicit transformation of vertical or torsional postrotatory responses towards alignment with gravity (Angelaki and Hess, 1994). Such difficulties, as well as previous reports that vertical optokinetic afternystagmus does not reorient relative to gravity have been taken as arguments against the existence of inertial vestibular signals (Dai et al, 1991;Raphan et al, 1994).…”
mentioning
confidence: 95%